Spanish as the Kana for Taiwan Southern Min - Richie, L. C. Chen (Penerbit UKM, 2012)
Taiwan Southern Min is the mother language for over 16 million people in Taiwan.However, due to a lack of a proper educational system, the use of Southern Min is drastically decreasing. Orthographic systems such as those based on Latin alphabets designed by the European missionaries, Japanese syllabaries by the Japanese government and then Mandarin Phonetic Symbols by the current Kuomintang government have been proposed to transcribe Taiwan Southern Min, but none has become popular or practical enough for a language promotion purpose. Spanish is among the most popular languages in the world, and had once been used as the phonetic system for Southern Min during the 16th and 17th century. From the incunabula such as Doctrina christina en letra y lengua china, Southern Min was expressed in the Spanish way with the diacritical marks such as those for aspiration and nasalization being used sporadically. The author believes that is the result of the similarity between Spanish and Southern Min in terms of pronunciation.Since the pronunciation of Spanish can be precisely determined by its alphabet, Spanish may become a handy platform for romanizing Southern Min. To construct a phonetic system based on Spanish, the author started by simulating the orthographic system of a similar language, the Japanese. By including several minor adaptations such as (1)expressing aspiration and nasalization by h and ñ (2) introducing the sixth vowel or and (3) modifying the usage of ch, Spanish was proven to be able to simulate the pronunciation of Taiwan Southern Min as the Kana system is to Japanese.